2005
DOI: 10.1074/jbc.m412741200
|View full text |Cite
|
Sign up to set email alerts
|

Signal-dependent Binding of the Response Regulators PhoP and PmrA to Their Target Promoters in Vivo

Abstract: Low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 26 publications
5
92
0
Order By: Relevance
“…7A, which is published as supporting information on the PNAS web site). A strain defective in PhoP's cognate sensor kinase PhoQ did not accumulate the RpoS protein during logarithmic growth in low Mg 2ϩ (data not shown), consistent with PhoQ's established role in activation of the PhoP protein (31,43). On the other hand, near wild-type RpoS levels were detected in a strain deleted for the phoQ gene but harboring an allele of phoP (termed phoP*) that promotes transcription of PhoP-activated genes independently of PhoQ (43) (data not shown).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…7A, which is published as supporting information on the PNAS web site). A strain defective in PhoP's cognate sensor kinase PhoQ did not accumulate the RpoS protein during logarithmic growth in low Mg 2ϩ (data not shown), consistent with PhoQ's established role in activation of the PhoP protein (31,43). On the other hand, near wild-type RpoS levels were detected in a strain deleted for the phoQ gene but harboring an allele of phoP (termed phoP*) that promotes transcription of PhoP-activated genes independently of PhoQ (43) (data not shown).…”
Section: Resultssupporting
confidence: 58%
“…The sensor protein PhoQ responds to low Mg 2ϩ by promoting phosphorylation of the response regulator PhoP (28)(29)(30)(31), which binds to its target promoters to stimulate transcription of PhoP-activated genes (24,32). The Salmonella PhoP͞PhoQ system controls expression of Ϸ3% of the genome (33).…”
mentioning
confidence: 99%
“…Furthermore, the steady-state behavior of the PhoQ/PhoP circuit with such a mutant should be strongly dependent on autoregulation, even for levels of stimulus where autoregulation has no effect on the behavior of the circuit with wild-type PhoQ. To test this, we used a PhoQ(T281R) mutant, which was predicted to have defective phosphatase activity (29). When we compared the activities of cytoplasmic fragments of wild-type PhoQ and PhoQ(T281R) in vitro, we found that PhoQ(T281R) showed slower PhoP phosphorylation and no observable PhoP-P dephosphorylation activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PmrD protein is produced when the sensor protein PhoQ responds to low extracytoplasmic Mg 2ϩ by promoting phosphorylation of the DNA-binding protein PhoP. The phosphorylated PhoP protein then binds to a large number of target promoters, including that of the pmrD gene, and activates or represses gene transcription (9,10). Three of the PmrA-activated loci mediate resistance to the antibiotic polymyxin B.…”
mentioning
confidence: 99%